The effect of online service quality and consumers’ motivation on willingness to participate in co-creation activities - Agnes Gracia Quita; Sahid Susilo Nugroho (Jurnal Siasat Bisnis, 2019)
This study examines factors that encourage consumers to participate in co-creation activities. There are two factors that have been tested concerning their roles in determining the willingness of consumers to participate in co-creation activities. The first factor comprise the system and techonology of the service provider. Those are reflected in availability, privacy, and responsiveness aspects of the e-service quality. The second factor is consumer behavior. It is reflected in social motivation and financial motivation aspects. This study applied a survey method using a purposive sampling method to interview 303 respondents. Data were obtained through an online survey. The proposed hypotheses are tested using multiple regression analyses. The study finds that availability, responsiveness, and social motivation have positive impacts on the willingness of consumers to participate in co-creation activities. Conversely, privacy and financial motivation have no effect at all.